1985
DOI: 10.1073/pnas.82.9.2565
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific recognition of B-DNA by oligo(N-methylpyrrolecarboxamide)s.

Abstract: Four homologous oligopeptide-EDTA molecules, tri-, tetra, penta-, and hexa(N-methylpyrrolecarboxamide)-EDTA, in the presence of Fe(II), 02, and dithiothreitol, cleave 32P-end-labeled restriction fragments from plasmid pBR322 DNA at common locations rich in A-T base pairs that differ in the size of the binding site. From analysis of the cleavage patterns visualized by high-resolution denaturing gel electrophoresis, the oligopeptides with three, four, five, and six Nmethylpyrrolecarboxamide units, containing fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 22 publications
(45 reference statements)
0
45
0
Order By: Relevance
“…The relevance of these two biophysical model studies to native DNA was demonstrated by the Dervan group. Their "footprinting" investigations revealed that netropsin binds to similar AT-rich sites of five base pairs in naturally occurring DNA polymers (8)(9)(10).…”
mentioning
confidence: 99%
“…The relevance of these two biophysical model studies to native DNA was demonstrated by the Dervan group. Their "footprinting" investigations revealed that netropsin binds to similar AT-rich sites of five base pairs in naturally occurring DNA polymers (8)(9)(10).…”
mentioning
confidence: 99%
“…The 2:1 motif has proven versatile, whereby pairs of amino acids can be assembled side-by-side to distinguish all four Watson⅐Crick base pairs (Im͞Py ϭ G⅐C; Py͞Im ϭ C⅐G; Hp͞Py ϭ T⅐A; and Py͞Hp ϭ A⅐T) (3). Py-Im polyamides are overcurved with respect to the DNA helix (4)(5)(6). By substituting the aliphatic amino acid ␤-alanine (␤) for Py, the ligand curvature is reset, allowing specific recognition of 16 contiguous base pairs of DNA (7)(8)(9).…”
mentioning
confidence: 99%
“…In some exceptional cases, the ligand in this 'reverse' polarity also results in some (a little) breakage in to labelled (top) strand. The fact that these cleavage sites seem to be almost 'within' the binding sites, is a consequence of the 'staggered' nature of the DNA helix (28), across the axis of the minor groove.…”
Section: Discussionmentioning
confidence: 99%